The Impact Of Digital Platforms On Mother Tongue Preservation: Challenges And Opportunities In The Disruption Era - Loso Judijanto; Fatima Malik; Dulguun Amarsaikhan (Yayasan Adra Karima Hubbi, 2025)
Background. In the disruption era, the rapid expansion of digital platforms has transformed communication, learning, and cultural exchange, creating both challenges and opportunities for preserving mother tongues. Globalized content consumption and dominant language use in digital spaces often marginalize minority languages, accelerating linguistic erosion. Purpose. This study aims to investigate the impact of digital platforms on mother tongue preservation, focusing on the balance between technological threats and revitalization potential. Method. A qualitative descriptive approach was employed, combining literature review and case analysis of digital initiatives promoting local languages. Data were collected from scholarly publications, online communities, and interviews with language activists. Results. Findings reveal that while unregulated exposure to dominant languages can weaken intergenerational transmission, digital tools such as social media campaigns, e-learning applications, and digital archives offer innovative pathways for documentation, education, and community engagement. Conclusion. The study concludes that strategic integration of cultural values with technology can transform digital platforms into allies for mother tongue preservation. Policy support, community participation, and localized content production are critical to sustaining linguistic diversity in the digital age.